Assessment of the intra-annual flow distribution of the Shu-Talas river basin over the past decade (Journal of Geography and Environmental Management, 2021)
Based on the collection and analysis of hydrological and meteorological data, the article estimates the distribution of intra-annual runoff within the Shu-Talas River basin over the past decades. To assess changes in the intra-annual distribution of runoff in the Shu-Talas water management basin, observation data for 10 active hydrological posts were collected from hydrological yearbooks. Limiting and non-limiting periods are established for the studied basin, including the period of predominance of meltwater runoff, the period of predominance of the rain source of food and the period of manifestation of ice phenomena. Empirical and analytical curves are constructed for each set period. According to these curves, three gradations of water content are defined: a high-water year (p33.3%) and are classified by water content of years in three groups. The intra-annual distribution of runoff over the past decades was estimated, and the results of the studies were compared and analyzed with the results given in the" Surface Water Resources of the USSR " for the basin under consideration. The calculations carried out allow us to determine various water management parameters for the basin, to ensure the safety of settlements within the basin.
Keywords: intra-annual distribution, average monthly water consumption, climate change, flood, lemitating period, non-lemitating period, empirical curve, analytical curve.